Leaf structure of curaua in different intensities of photosynthetically active radiation - Oliveira, Elaine Cristina Pacheco de; Lameira, Osmar Alves; Sousa, Fernanda Ilkiu Borges de; Silva, Rolf Junior Ferreira (Pesquisa Agropecuaria Brasileira, 2008)
The aim of this work was to characterize the leaf anatomy of Ananas comosus var. erectifolius and to compare the anatomical characterists of its leaf fibres, when submitted to two levels of photosynthetically active radiation (54 and 100%). For the analysis of the anatomical structures, specially the fibres, the settled botanical material was submitted to techniques of dissociation of the foliar epidermis, microscopic number of stomata per square millimeter, cuts and scanning electron microscopy. The epidermis was coated for thick cuticle and developed well in leaves in the two intensity indexes of radiation. For leaves at 100% PAR a fast increase of thickness was observed in the apical and basal regions. Regarding the radiation levels, differences were observed in the number of layers, the height of palisade parenchyma, and in the amount of fibre beams. The amount of fibre beams was bigger at 54% than at 100% PAR.
Keywords: Ananas comosus; plant anatomy; Bromeliaceae; vegetable fibre